Предмет: Алгебра,
автор: marinabulftyfy
(х-1)²/5-х+4/6=2х-2/3 решить уравнение
Ответы
Автор ответа:
0
(х-1)²/5-(х+4)/6-
(2х-2)/3
=0
Приведем к общему знаменателю:
(6(x-1)^2-5(x+4)-10(2x-2))*30=0 |*30
6(x-1)^2-5(x+4)-10(2x-2)=0
Приведем подобные:
6x^2-12x+6-5x-20-20x+20=0
6x^2-37x+6=0
D=1369-144=1225
х=(37+-35)/12
х1=6
х2=1/6
Приведем к общему знаменателю:
(6(x-1)^2-5(x+4)-10(2x-2))*30=0 |*30
6(x-1)^2-5(x+4)-10(2x-2)=0
Приведем подобные:
6x^2-12x+6-5x-20-20x+20=0
6x^2-37x+6=0
D=1369-144=1225
х=(37+-35)/12
х1=6
х2=1/6
Похожие вопросы
Предмет: Английский язык,
автор: yoursweatlie
Предмет: Математика,
автор: Аноним
Предмет: Алгебра,
автор: bignunaspi
Предмет: Математика,
автор: Dnma5
Предмет: Математика,
автор: pipex23